Correlations between ligand field Δo, spin crossover T1/2 and redox potential Epa in a family of five dinuclear helicates. Issue 32 (21st July 2021) - Singh, Sandhya; Brooker, Sally
Abstract : Choice of non-coordinated diazole heteroatom in five robust triply bridged dinuclear helicates tunes Δ o, spin crossover and redox potential. Regardless of fraction high spin (0–0.81), DOSY NMR confirms the helicates are intact in solution. Abstract : A family of five new bis-bidentate azole–triazole Rat ligands (1, 3-bis(5-(azole)-4-isobutyl-4 H -1, 2, 4-triazol-3-yl)benzene), varying in choice of azole (2-imidazole, 4-imidazole, 1-methyl-4-imidazole, 4-oxazole and 4-thiazole), and the corresponding family of spin-crossover (SCO) and redox active triply bridged dinuclear helicates, [FeII2L3 ] 4+, has been prepared and characterised. X-ray crystal structures show all five Fe(ii ) helicates are low spin at 100 K. Importantly, DOSY NMR confirms the intactness of these SCO-active dinuclear helicates in D3 -MeCN solution, regardless of HS fraction: γ HS (298 K) = 0–0.81. Variable temperature 1 H NMR Evans and UV-vis studies reveal that the helicates are SCO-active in MeCN solution. Indeed, the choice of azole in the Rat ligand used in [Fe2 L3 ] 4+ tunes: (a) solution SCO T 1/2 from 247 to 471 K, and (b) reversible redox potential, E m (Fe II/III ), from 0.25 to 0.67 V for four helicates, whilst one has an irreversible redox process, E pa = 0.78 V, vs. 0.01 M AgNO3 /Ag. For the four reversible redox systems, a strong correlation ( R 2 = 0.99) is observed between T 1/2 and E pa . Finally, the analogous Ni(ii ) helicates have been prepared to obtain Δ o, establishing: (a) the ligand field strength order of the ligands: 4-imidazole (11 420) ∼ 1-methyl-4-imidazole (11 430) < 2-imidazole (11 505) ∼ 4-oxazole (11 516) < 4-thiazole (11 804 cm −1 ), (b) that Δ o ([Ni II 2 L3 ] 4+ ) strongly correlates ( R 2 = 0.87) with T 1/2 ([FeII2L3 ] 4+ ), and (c) interestingly that Δ o strongly correlates ( R 2 = 0.98) with E pa for the four helicates with reversible redox, so the stronger the ligand field strength, the harder it is to oxidise the Fe(ii ) to Fe(iii ).